1949
DOI: 10.1021/ja01171a051
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Behavior of Hexachlorocyclopentadiene. I. Transformation to Octachloro-3a,4,7,7a-Tetrahydro-4,7-methanoindene-1,8-dione

Abstract: mixture of 5.04 g. (0.022 mole) of phloroglucinol and 3.96 g. (0.04 mole) of maleic anhydride in 45 cc. of nitrobenzene was cooled to 10°. During the course of 15 minutes 17.42 g. (0.13 mole) of anhydrous aluminum chloride was introduced with mechanical stirring. External cooling was needed to keep the temperature at 30°. After 0.5 hr. the exothermic reaction subsided and the mixture was stirred at room temperature for 0.75 hr. The aluminum complex was decomposed in a mixture of ice and concentrated hydrochlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

1958
1958
2006
2006

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(28 citation statements)
references
References 0 publications
1
26
0
1
Order By: Relevance
“…Some of the results of thermal studies are shown in Table 1. An effort was then made to incorporate a larger group on one of the apex carbons; this was achieved by causing hexachlorocyclopentadiene to react with HSO3C1 thereby making a chlorosulfonate (V), C10C1HOSOaCI (Newcomer & McBee, 1949a). Since the chlorosulfonate thus obtained can easily be transformed into the cage…”
Section: Introductionmentioning
confidence: 99%
“…Some of the results of thermal studies are shown in Table 1. An effort was then made to incorporate a larger group on one of the apex carbons; this was achieved by causing hexachlorocyclopentadiene to react with HSO3C1 thereby making a chlorosulfonate (V), C10C1HOSOaCI (Newcomer & McBee, 1949a). Since the chlorosulfonate thus obtained can easily be transformed into the cage…”
Section: Introductionmentioning
confidence: 99%
“…The starting compounds 1 and 2 were prepared according to procedures described earlier. 1,4 (1R*,2S*) 2,4,5,6,7 Pentachloroindan 1 ol (3). A solution of diketone 1 (0.52 g, 1.19 mmol) in EtOH (5 mL) was added dropwise to a stirred suspension of 85% NaBH 4 (0.26 g, 5.85 mmol) in ethanol (5 mL) at 0 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Le cyclopentadiene utilisC a 6tC prCpare par distillation du bicyclopentadiene commercial. Le pentachlorocyclopentadiBne a CtC prtparC partir d'hexachlorocyclopentadiene par la rnethode dCcrite par Newcomer et McBee (19).…”
Section: Indications Gdndralesunclassified